Pengaruh Respon Pertumbuhan Benih Ikan Bileh (Rasbora sp.) yang Dipelihara pada Suhu Berbeda - Irhami S; Agusriati Muliyana; Fitria Rahmayanti; Muktaridha Muktaridha (Jurnal Galung Tropika, 2026)
Bileh fish (Rasbora s.) is a freshwater species with high economic value and strong potential to be developed as an aquaculture commodity through domestication efforts to reduce exploitation pressure on wild populations. One of the key environmental factors influencing the success of domestication is rearing temperature, as it directly affects physiological processes and metabolic activity in fish. This study aimed to evaluate the growth response of bileh fish juveniles reared at different temperatures under controlled aquaculture conditions. The experiment was conducted at the Hatchery of the Faculty of Fisheries and Marine Sciences, Teuku Umar University, from July to August 2025 for a period of 40 days. A Completely Randomized Design was applied with four temperature treatments, namely 20°C (P1), 24°C (P2), 28°C (P3), and 32°C (P4), each with three replications. The observed parameters included absolute weight gain, absolute length gain, relative growth rate, and water quality parameters (temperature and pH). The results demonstrated that rearing temperature had a significant effect (P<0.05) on the growth performance of bileh fish juveniles. Optimal growth was achieved at 24°C (P2), with an absolute weight gain of 0.45 g, an absolute length gain of 2.1 cm, and a relative growth rate of 1.13%. In contrast, the 32°C treatment resulted in the lowest growth performance and greater pH variability (6–8). Temperature plays a critical role in fish metabolism, where excessively high temperatures increase energy demands for maintaining homeostasis, thereby limiting energy allocation for growth. Therefore, a rearing temperature of 24°C is recommended as the optimal condition for the culture of bileh fish juveniles.